KEDUDUKAN DAN FUNGSI LEMBAGA PERWAKILAN RAKYAT DALAM SISTEM PRESIDENSIAL - Thaher, Irmanjaya (Gapenas Publisher, 2024)
The people's representative institution is a key pillar of modern constitutional democracy, serving as the formal representation of the will of the people in the exercise of state power. In a presidential system, this institution holds a unique position as an equal partner to the executive, with democratic legitimacy derived from an independent electoral mandate.This study comprehensively analyzes the position and function of the House of Representatives (DPR) in Indonesia's presidential system through four dimensions: constitutional construction and inter-institutional relations, the effectiveness of the legislative function, the strength of the oversight function as a mechanism of checks and balances, and the identification of an institutional reform agenda to optimize the DPR's role sustainably.The research methodology employed a Systematic Literature Review (SLR) conducted systematically, structured, and transparently to identify, evaluate, and synthesize various relevant scholarly articles to generate a comprehensive, evidence-based understanding of conceptual developments and empirical findings.The results indicate that the DPR holds a strong constitutional position and is equal to the President, with a collaborative relationship based on the principle of proportional distribution of power. The legislative function, as the core of the DPR's constitutional role, still faces challenges in terms of productivity and quality of legislation, requiring institutional capacity strengthening. The oversight function, through the right of inquiry, is a vital mechanism for maintaining checks and balances, requiring consistent implementation to achieve true executive accountability.The study concludes that multidimensional institutional reform, encompassing structural, legal, and representative capacity aspects, is an urgent step to ensure representative institutions are able to carry out their constitutional functions optimally and sustainably. Strengthening checks and balances and improving the quality of legislation are fundamental prerequisites for optimizing the role of the DPR in Indonesia's democratic and just presidential system.